Chi-circ_0009659 modulates goat intramuscular adipocyte differentiation through miR-3431-5p/STEAP4 axis - Xin Li; Hao Zhang; Yong Wang; Yanyan Li; Youli Wang; Yan Xiong; Wei Liu; Yaqiu Lin (Animal Bioscience)
Objective Circular RNAs (circRNAs) are widely involved in the regulation of lipid deposition in animals, but there are few reports on key circRNAs regulating intramuscular adipocyte differentiation in goats. Therefore, this study took an abundantly expressed in goat adipocytes chi-circ_0009659 as the object. Methods Based on the identification of back splicing site in chi-circ_0009659, its expression level during the goat intramuscular preadipocyte differentiation was detected by quantitative polymerase chain reaction (qPCR) . The chi-circ_0009659 loss-of-function and gain-of-function cell models were obtained by adenovirus and smarter silencer, respectively. and the adipocyte differentiation were explored by Oil Red O staining, Bodipy staining and qPCR. Its major cytoplasmic localization was determined by fluorescence in situ hybridization (FISH), nucleocytoplasmic separation and qPCR. The interaction between chi-circ_0009659, miR-3431-5p, and STEAP family member 4 (STEAP4) was verified by bioinformatics, RNA pull down and dual luciferase reporter assay. Results Silencing chi-circ_0009659 inhibited lipid droplet accumulation and the expression of differentiation-determining genes in goat intramuscular adipocytes, while overexpression of chi-circ_0009659 reversed these results. chi-circ_0009659 was predominantly localized to the cytoplasm and could regulate miR-3431 expression which in turn affects STEAP4. Consistent with expectations, miR-3431-5p acted as a negative regulator of GIMPA differentiation, while STEAP4 promoted differentiation. Conclusion We demonstrated chi-circ_0009659 positively regulates goat intramuscular preadipocyte differentiation by sponging miR-3431-5p to further regulate the expression of STEAP4. This research provides a new reference for in-depth understanding of the effects of circRNA on adipocyte differentiation.